Caracterización del proceso de compra emocional del consumidor lojano - Mendoza Pasaca, Milena Escarlet (2024)
The emergence of neuromarketing raises a fascinating question: What really drives consumer purchasing decisions? This research delves into the enigma of knowing the behavior of lojano consumer, exploring how the synergy between the senses and emotions shapes and guides the purchasing process. Through a meticulous exploratory- descriptive design, combining analysis of primary and secondary sources, including detailed surveys of 400 participants distributed equally among key generations – such as baby boomers, millennials, generation that: sight dominates advertising influence, and emotions play a crucial role, unconsciously and silently guiding purchasing decisions. This research not only confirms the intrinsic complexity of consumer behavior, but also reveals the hidden power of sensory and emotional stimuli in shaping purchasing preferences. The implications for marketing are profound, offering new avenues to capture the attention and heart of the consumer. By understanding these underlying mechanisms, brands can design strategies that create shopping experiences that not only satisfy, but delight, fostering a deeper, more lasting connection with their consumers. The main objectives seek to evaluate the influence of sensory marketing on consumer purchasing decisions in Loja. On the other hand, identify the emotional factors that influence the purchasing decisions of Loja consumers. Finally, provide recommendations for the effective implementation of neuromarketing strategies in local companies in the city as a contribution to their development, allowing a path different from the traditional one.